212Pb-conjugated anti-rat HER2/neu antibody against a neu-N derived murine mammary carcinoma cell line: cell kill and RBE in vitro. (2nd September 2022) - Liatsou, Ioanna; Yu, Jing; Bastiaannet, Remco; Li, Zhi; Hobbs, Robert F.; Torgue, Julien; Sgouros, George
Abstract: Purpose: In the current work, the RBE of a 212 Pb-conjugated anti-HER2/ neu antibody construct has been evaluated, in vitro, by colony formation assay. The RBE was estimated by comparing two absorbed dose-survival curves: the first obtained from the conjugated 212 Pb experiments (test radiation), the second obtained by parallel experiments of single bolus irradiation of external beam (reference radiation). Materials and Methods: Mammary carcinoma NT2.5 cells were treated with (0–3.70) kBq/ml of radiolabeled antibody. Nonspecific binding was assessed with addition of excess amount of unlabeled antibody. The colony formation curves were converted from activity concentration to cell nucleus absorbed dose by simulating the decay and transport of all daughter and secondary particles of 212 Pb, using the Monte Carlo code GEANT 4. Results: The radiolabeled antibody yielded an RBE of 8.3 at 37% survival and a survival independent RBE (i.e. RBE2) of 9.9. Unbound/untargeted 212 Pb-labeled antibody, as obtained in blocking experiments yielded minimal alpha-particle radiation to cells. Conclusions: These results further highlight the importance of specific targeting toward achieving tumor cell kill and low toxicity to normal tissue.